Association of Acute Postoperative Pain and Cigarette Smoking With Cerebrospinal Fluid Levels of Beta-Endorphin and Substance P - Wang, Fan; Li, Hui; Mu, Qingshuang; Shan, Ligang; Kang, Yimin; Yang, Shizhuo; Chang, Hui-Chih; Su, Kuan-Pin; Liu, Yanlong (Frontiers in Molecular Neuroscience, 2022)
Objectives: Cigarette smoking is associated with postoperative pain perception, which might be mediated by beta-endorphin and substance P. These effects on postoperative pain perception have never been investigated in human cerebrospinal fluid (CSF), which reflects biochemical alterations in the brain. Therefore, we investigated the associations among cigarette smoking, postoperative pain, and levels of beta-endorphin and substance P in human CSF. Methods: We recruited 160 Chinese men (80 active smokers and 80 nonsmokers) who underwent lumbar puncture before anterior cruciate ligament reconstruction, and 5-ml CSF samples were collected. Pain visual analog scale (VAS) scores, post-anesthetic recovery duration (PARD), and smoking variables were obtained. CSF levels of beta-endorphin and substance P were measured. Results: Compared to non-smokers, active smokers had significantly higher pain VAS (2.40 ± 0.67 vs. 1.70 ± 0.86, p < 0.001) and PARD scores (9.13 ± 2.11 vs. 7.27 ± 1.35, p = 0.001), lower CSF beta-endorphin (33.76 ± 1.77 vs. 35.66 ± 2.20, p = 0.001) and higher CSF substance P (2,124.46 ± 217.34 vs. 1,817.65 ± 302.14, p < 0.001) levels. Pain VAS scores correlated with PARD in active smokers (r = 0.443, p = 0.001). Conclusions: Cigarette smoking is associated with increased postoperative pain intensity, shown by delayed pain perception, higher pain VAS scores, and lower beta-endorphin and higher substance P levels in the CSF of active smokers. The more extended postoperative pain perception is delayed, the more pain intensity increases.